The Concept of Critical Thinking Based on Ulul Albab in the Qur'an and Its Implementation at the Asshiddiqiyah 3 Karawang Islamic Boarding School - Aulia Nurfadilah; Debibik Nabilatul Fauziah; Neng Ulya (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
There are quite a few Islamic boarding schools that still apply Critical Thinking skills in their learning, including the Asshiddiqiyah 3 Karawang Islamic Boarding School, an Islamic educational institution located in the Cilamaya Wetan area, Karawang Regency. Based on pre-research observations made by the author, the implementation of the concept of Critical Thinking at the Asshiddiqiyah 3 Karawang Islamic Boarding School. This research aims to (1) To find out the interpretation of Surah Al Imran verses 190-191 and Surah Az Zumar verse 18 according to commentators (2) To find out the concept of Critical Thinking based on the Ulul Albab in Surah Al Imran verses 190-191 and Surah Az Zumar verse 18 based on the interpretation of commentators (3) To find out the implementation of the concept of Critical Thinking in Al Imran verses 190-191 and Az Zumar verse 18 towards students at the Asshiddiqiyah 3 Karawang Islamic Boarding School. In this research, an approach is used which is known as a qualitative approach because it shows a description of the phenomenon regarding teachers' and students' responses to the concept of Critical Thinking based on Ulul Albab in the Al-Qur'an and its implementation at the Asshiddiqiyah 3 Karawang Islamic Boarding School. The results of this research show that the Tafsir of Surah Al Imran verses 190-191 and Surah Az Zumar verse 18 emphasizes the importance of Critical Thinking for humans. The concept of Critical Thinking based on Ulul Albab in these verses is based on the interpretation of Ibn Kathir's tafsir, Al-Azhar tafsir, and Al Misbah tafsir, which combines Islamic values ​​of wisdom, Critical Thinking, and good decision making.